Impact of sex and age on adherence to guidelines in non-small cell lung cancer management - Paakkola Nelly-Maria; Lindqvist Jonatan; Jekunen Antti; Sihvo Eero; Johansson Mikael; Andersén Heidi (Elsevier, 2025)
Introduction
Age-related disparities in non-small cell lung cancer (NSCLC) treatment are well known, but few studies have assessed the impact of sex on treatment disparities. Disparities in guideline-adherence may explain the superior survival in women with NSCLC. Therefore, we aimed to define patient- and tumor-related factors associated with non-adherence to guidelines in NSCLC management with a special focus on sex and age.
Patients and Methods
Patients with NSCLC who received first-line treatment at the Vaasa Central Hospital between 2016 and 2020 were included in the study. The primary outcome was guideline adherence, defined as adherent, undertreatment, or overtreatment considering performance status. A binary logistic regression model was used to calculate the adjusted odds ratio (aOR) for non-adherence to treatment guidelines depending on patient- and tumor-related factors.
Results
321 patients were included in the study. Non-adherence was highest in ≥75-year-old women (41.3%), followed by ≥75-year-old men (32.6%), <75-year-old men (27.6%) and lowest in women <75-year-old (19.7%) (p = 0.035). Non-adherent care consisted more often of undertreatment in <75-year-old men than women (26.0% versus 12.1%) and overtreatment in <75-year-old women than men (7.6% versus 1.6%). Non-adherence was associated with stage III disease (aOR 2.21; 95% CI 1.07–4.59), poor pulmonary function (aOR 3.69, 95% CI 1.56–8.71), and Charlson Comorbidity Index 1–2 (aOR 2.09; 95% CI 1.09–4.01).
Conclusion
Sex- and age-related disparities in guideline adherence were observed in <75-year-old men and in ≥75-year-olds. Stage III NSCLC was associated with non-adherence.